Antibiotics as Emerging Pollutants in Water and Its Treatment - Sanchez-Poblete, J; Godoy-Perez, M (Elsevier, 2020)
Emerging pollutants are compounds of different origin and chemical nature, essentially organic compounds or artificial chemicals such as personal care products, surfactants, plasticizers, industrial additives, and pharmaceutically active compounds as hormones, steroids, lipid regulators, and antibiotics. Antibiotics are not yet considered in water treatment programs nor are they monitored. According to the World Health Organization, there are currently few systematic follow-up programs and full studies on human exposure to antibiotics in drinking water. In addition, its presence in the environment goes unnoticed because its distribution is random and its concentrations are low. At present, environmental studies have detected their presence in surface waters, raising questions about their potential environmental impact and human health. Some scientific research works have focused on how to extract these products from aqueous effluents. The antibiotics of the β-lactam family, as well as those belonging to the fluoroquinolone family, have been of great interest in these investigations due to their wide use in both human and veterinary medicine. Nowadays exists several techniques and methods applied in the study of the removal and/or degradation of antibiotics such as advanced oxidation processes, ultrasonic irradiation, combined treatments, and solid-liquid separation processes through complexing sorbents or ion exchange. Sorption is promising in antibiotic removal due to its ease of implementation and efficiency. One of the advantages of solid-liquid extraction systems with sorbents is the separation of both phases in a simple way by physical processes. In this context, the new sorbent materials as activated carbon, carbon nanotubes, and graphene, among others, have been used for the remediation of aqueous matrices with different antibiotics. On the other hand, some polymers and membranes have been tested on selective removal of antibiotics. The use of these materials is quite effective, over 90% efficiency in some cases, which depends on experimental variables such as pH, temperature, and pressure. More recently ultrafiltration and water-soluble polymers have been used in combination with a hybrid separation system called polymer-enhanced ultrafiltration. This technique was efficient and selective for the removal of antibiotics (ciprofloxacin) from aqueous streams. It is important that the scientific community develops more studies in this field because the water sources are more limited worldwide and the number of emerging pollutants as antibiotics are increasing in aqueous systems. © 2020 Elsevier Inc. All rights reserved.